Respuesta :

18 + 3(9f - 13)
Use distributive property
18 + 27f - 39
Subtract 39 from 18
Final Answer: 27f - 21 or 9f - 7 *Both answers are equivalent to each other.
Simplifying: 18 + 3(9f + -13) = 0

Reorder the terms: 18 + 3(-13 + 9f) = 0
18 + (-13 * 3 + 9f * 3) = 0
18 + (-39 + 27f) = 0

Combine like terms: 18 + -39 = -21 -21 + 27f = 0

Solving: -21 + 27f = 0

Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right.

Add '21' to each side of the equation. -21 + 21 + 27f = 0 + 21

Combine like terms: -21 + 21 = 0
0 + 27f = 0 + 21
27f = 0 + 21

Combine like terms: 0 + 21 = 21
27f = 21

So 18 + 3(9f - 13) = 27f - 21

Hope I Helped ; )